The Influence of Toxic Parenting on Social Anxiety and Social Skills of SMAN Batusangkar Students - Rafsel Tas'adi; Dasril Dasril; Fatih Hatil Yusra; Anindita Anindita; Irman Irman; Rina Yulitri; Wenda Asmita (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Toxic parenting is a type of parental behavior whose impact can destroy a child's life, both in individual and social contexts. The aim of this research is to determine the effect of toxic parenting on students' social anxiety and social skills. The research was conducted at SMAN 1 and 2 Batusangkar. The type of research used is quantitative descriptive. Sampling was taken using nonrandom sampling, namely the accidental convenience sampling technique. Data collection uses a Likert scale. Data analysis with Regression. The research results show that toxic parenting has a significant effect on students' psychology, namely on social anxiety and social skills. The higher the toxic parenting, the higher the student's social anxiety and the lower their social skills. It is highly hoped that parents will have a high level of awareness to abandon toxic behavior in their parenting patterns.